2007
DOI: 10.1242/jeb.004101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osmotic shrinkage and hormones on the expression of Na+/H+ exchanger-1,Na+/K+/2Cl– cotransporter and Na+/K+-ATPase in gill pavement cells of freshwater adapted Japanese eel,Anguilla japonica

Abstract: the regulation is rapid and is probably induced via nongenomic actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…Our previous study demonstrated hypertonic-induced cell shrinkage, RVI and the expression of Ostf (Tse et al, 2007;Tse et al, 2008). In this study, using immunocytochemical staining, our data indicate that hypertonic treatment induced an increase in F-actin staining at the periphery of the hypertonic-treated gill cells.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our previous study demonstrated hypertonic-induced cell shrinkage, RVI and the expression of Ostf (Tse et al, 2007;Tse et al, 2008). In this study, using immunocytochemical staining, our data indicate that hypertonic treatment induced an increase in F-actin staining at the periphery of the hypertonic-treated gill cells.…”
Section: Discussionsupporting
confidence: 70%
“…Gill arches were excised and some gill filaments were directly dissolved in Trizol solution for total RNA extraction or fixed in 4% paraformaldehyde (PFA, Sigma, St Louis, MO, USA) for immunohistochemistry. Other gill tissues were cut into small fragments and were subjected to two cycles of tryptic digestion (0.5% trypsin+5.3 mmol l -1 EDTA) for the establishment of primary gill cell culture as previously described (Tse et al, 2007;Tse et al, 2008). After tryptic digestion, the cell suspension was filtered and washed.…”
Section: Animals and Gill Cell Isolationmentioning
confidence: 99%
“…These modulations of gene expression occurred in response to plasma osmotic conditions routinely experienced during the acute phases of FW (~280 mOsm/kg) and SW (~450 mOsm/kg) acclimation (Inokuchi et al 2015). Hyperosmotic conditions stimulate the gene expression of Na + /K + /2Cl − cotransporter 1a (nkcc1a), a key cotransporter underlying ion extrusion by teleost ionocytes , Inokuchi et al 2015, as well as volume regulation by pavement cells (Tse et al 2007). Thus, enhanced aqp3/Aqp3 expression in the basolateral region of branchial cells in FW-acclimated tilapia (Fig.…”
Section: :3mentioning
confidence: 99%
“…The evolved capacities of these 'euryhaline' fishes to tolerate disparate salinities necessitate that epithelial surfaces in direct contact with external conditions possess sensory systems that detect changes in ambient osmolality (Fiol & Kültz 2007). These osmosensory systems couple with regulatory systems that both protect cellular homeostasis and modulate the expression of ion transport effectors responsible for maintaining homeostasis of the organism (Fiol & Kültz 2007, Tse et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The results of recent research underline the importance of the physiological role of the described mechanism, directly conjugated with the basic homeostatic functions of the gill apparatus, ensuring the stability of the parameters of gas exchange, acid-base and osmotic balance of internal environment (Evans et al 2005). However, some authors ascertain the relevance of further research, whose aim is, firstly, the creation of adequate models of clearance of ammonia, which is closely associated with the work of the ion-transporting systems of gill epithelium (Wright and Wood Ch 2009), in-Second, the analysis of physiological and evolutionary aspects of the ways renal clearance of ammonia in fish (Nakada et al 2007), as well as to study the features of neuro-humoral control systems of homeostatic functions of the gill apparatus of fish (Hoshijima and Hirose Sh 2007;Tse et al 2007). …”
Section: Introductionmentioning
confidence: 99%